A community service doctor’s experiences of mental healthcare provision in rural Eastern Cape - Divan Rall; Leslie Swartz (South African Family Practice)
Background: Literature shows that in South Africa there are insufficient resources to meet mental healthcare needs. At general or district hospital level, the non-specialist doctor is often responsible for the holistic assessment and management of mental health service users. Such situations inevitably increase doctors’ care load as they are required to treat across disciplines. We highlight the particular challenges faced by a community service (CS) doctor in this context.